Report of the joint select committee, on the subject of establishing a bank in the town of Henderson (House doc. (North Carolina. General Assembly. House of Commons) ;, 1841)
1841 report of the Joint Select Committee on the subject of establishing a bank in the town of Henderson, per a petition by some of its citizens. A bill to establish the Tobacco Planters' Bank of Henderson was attached to the report.